Growth parameters and leaf biomass yield of stevia (Stevia rebaudiana, Bertoni) as influenced by different soil types of Bangladesh (Journal of the Bangladesh Agricultural University, 2016)
Soils of different types affect crop production according to their capability as a nutrient supplier based on plant requirement. Soil provides physical support to plant as well as supplies necessary water and nutrient elements for plant growth and development. Suitable soil for stevia cultivation in Bangladesh is yet to be identified. A high concentrate sweetness producer plant, stevia (Stevia rebaudiana Bertoni) was grown in earthen pots in some soils of Bangladesh to choose the most suitable soil/s for the growth and leaf yield of stevia. Seven soil types namely acid, calcareous, non-calcareous, charland, saline, peat and acid sulphate were used as treatments. The soils were mostly light grey in colour and clay to clay loam in texture. Bulk density, particle density and field capacity ranged from 1.24-1.45, 2.20-2.58 and 27.03-30.19%, respectively. pH, EC and organic matter content ranged from 3.90-8.00, 0.25-14.00 dS m-1 and 0.88-16.40%, respectively. Total N, exchangeable K, available P and S contents ranged from 0.05-0.96%, 0.17-0.70 cmol kg-1 soil, 3-12 and 11-735 ?g g-1 soil, respectively. Different soil types significantly influenced the growth and leaf yield of stevia. The highest values of plant height, branch and leaf number, leaf area, fresh and dry weight of leaves were obtained from the plant grown in non-calcareous soil which was identical with the plant those grown on acid soil while the lowest values of all the parameters were found from the plant grown in acid sulphate soil. Leaf biomass yield increase ranged from 16.18% in peat soil and 90.11% in non-calcareous soil over acid sulphate soil. The performance of the soils in terms of stevia leaf production was of the order non-calcareous> acid> calcareous> charland> saline(4.43 dS m-1)> saline(6.08 dS m-1)> saline(8.68 dS m-1)> peat >acid sulphate soils. The overall results suggest that farmers could be advised to grow stevia either in non-calcareous soil or acid soils of Bangladesh.J. Bangladesh Agril. Univ. 13(1): 31-37, June 2015